Accessing the Carbofuran Degradation Ability of Cultures From Natural River Biofilms in Different Environments. Issue 5 (16th March 2017) - Tien, Chien‐Jung; Huang, Hsin‐Jan; Chen, Colin S.
Abstract : Acclimatized microbial consortia and bacterial strains were isolated from natural river biofilms to investigate their carbofuran degradation ability. Under 28‐day continuous enrichment culturing of river biofilms, the acclimatized microbial consortia were obtained and showed a high carbofuran removal rate (52.5%). The batch experiments showed that 28‐ and 35‐day loofah‐sponge‐attached acclimatized consortia ( i.e ., microbial consortia A and B) had low carbofuran removal rates. However, after preservation, the carbofuran degradation abilities of both microbial consortia recovered possibly due to the growth of carbofuran degraders. Denaturing gradient gel electrophoresis (DGGE) analysis revealed that Stenotrophomonas sp., Pseudomonas fulva, Comamonas jiangduensis, and Thermolithobacter sp. dominated in both microbial consortia. The best preservation conditions to have high carbofuran removal for microbial consortia A and B were −20°C for 3 months (55.7% removal) and 25°C for 1 month (73.9% removal), respectively. The isolated Sphingobacterium multivorum showed high carbofuran removal rates with and without sugar (67.4 and 73.1% removal) at pH 7 (25°C), followed by those at pH 7 (30°C) and pH 9 (25°C) (41.2 and 32.1% removal). This strain was able to degrade carbofuran in the simulated carbofuran‐contaminated paddy fields. The study demonstrated that the immobilized microbial consortia and S. multivorum from river biofilms are good biomaterials for bioremediating carbofuran‐contaminated sites. Abstract : The immobilized microbial consortia and Sphingobacterium multivorum isolated from river biofilms continuously cultured in the carbofuran‐enriched medium are good biomaterials for bioremediating carbofuran‐contaminated sites. Preservation of microbial consortia cause changes in their carbofuran degradation ability. The effects of environmental factors on the carbofuran degradation ability of S. multivorum are evaluated.